Anti-inflammatory properties of 3-(2,5-dimethoxyphenyl)-1-(5-methylfuran-2-yl) prop-2-en-1-one (L31) in lung epithelial cells and on airway inflammation in a murine model of asthma - Rajajendram, Revathee (2014)
Diverse heterocyclic compound’s production involved chalcones. Many studies have proven that chalcone derivative compound possess assorted biological activities such as antimicrobial, anti-inflammatory, analgesic, antiplatelet, antiulcerative, antimalarial, anticancer and antiviral properties. Cardamonin’s analogues 3-(2,5-dimethoxyphenyl)-1-(5-methylfuran-2-yl)prop-2-en-1-one (L31) was synthesized. Cell viability was resolved by conducting MTT cytotoxicity assay. L31 has a firm suppression effect upon eotaxin, MCP-1 and RANTES but did not inhibit the secretion of chemokines GRO-α and IL-8. The molecular target of L31 on several major proinflammatory pathways was furtherdissected. The results from western blots reveal that L31 targets the NF-kB but not the MAPK pathway. These findings confirm the selectivity and specificityof L31. Dose-response studies were conducted on female Balb/c mice in which doses (0.2, 2, 20 and 100 mg/kg) of L31 were administered intraperitoneally to mice following sensitization and aerosolized doses of ovalbumin (OVA). Mice were then subjected to methacholine challenge with an ultrasonic nebulizer and airway hyperresponsiveness was determined by comparison of enhanced pause (Penh) responses. Whole-body plethysmography system (Buxco) was used to measure the Penh value. Analysis of bronchoalveolar lavage (BALF) showed that all doses of L31 caused significant reduction in airway eosinophilia, tissue inflammatory scores and goblet cell metaplasia. L31 suppressed the secretion of eotaxin, RANTES, interleukin (IL) 4, IL 5 and IL 13.L31 also inhibits the gene expression of the all the mediator except for IL13. Collectively,these findings are vital in making decisions for further development of L31 compounds into anti-inflammatory and anti-asthmatic drug. The ultimate aim would be to enter clinical trials since the current therapy involves administration of combinations of steroids and β-agonists which in long term would mask untreated inflammation and lead to a higher risk of adverse outcomes.